PERANCANGAN DESTINATION BRANDING KAWASAN PANTAI PUCANGLABAN SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Nadya Cahya Faradita; Siswo Martono; Dhika Yuan Yurisma (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
One of the beaches in Tulungagung Regency known for its beautiful waves and pristine white sand is Pucanglaban Beach. It is suitable for swimming, sunbathing, or simply relaxing by the shore. This tourist destination is directly adjacent to the southern sea. The natural potential of Desa Pucanglaban encompasses the coastal area, including Pacar Beach, Kedung Tumpang Beach, and Molang Beach. The entrance fee to access this beach area is highly affordable, costing only Rp. 8,000, allowing visitors to enjoy all three beaches simultaneously. Facilities in the Pucanglaban Beach area include a mosque, restrooms, safety equipment, tent rentals, food and beverage stalls, parking facilities, and photo spots. However, despite the comprehensive facilities, this beach area lacks a strong brand identity. This research aims to design a destination branding strategy for the Pucanglaban Beach area with the goal of increasing brand awareness, contributing to the economic growth of Desa Pucanglaban, introducing the beauty and allure of Pucanglaban Beach to a wider audience, and creating a positive image. The design methodology used is design thinking, which involves various stages such as empathy, definition, ideation, prototype, and testing. The result of this design process is a key concept, namely